Larval Fish Assemblages on Ireland’s West Coast: Insights into Long-Term Community Shifts - Mohd Nasarudin, Harith; Khairul Adha, A. Rahim; Brendan, O’Hea; Anne Marie, Power; Nur Atiqah, Mohamad Yusoff. (The Egyptian Society for the Development of Fisheries and Human Health (ESDFHH), 2025)
This study aimed to maximize the value of historical ichthyoplankton data from the Mackerel Eggs Survey (MEGS) by examining changes in fish larval communities over a nine-year interval (2007 and 2016) along the west coast of Ireland. Larval distribution and composition in on-shelf and off-shelf areas were assessed using a GULF VII plankton sampler towed at four knots along a V-shaped transect. Sampling was conducted approximately five metres above the seabed, or to a maximum depth of 200m. A total of 1,397 fish larvae were collected in 2016 and 499 in 2007. In 2016, 43 species from 25 families were identified, compared with 27 species from 19 families in 2007. Cyclothone braueri (garrick) was the most abundant species in 2016, while Entelurus aequoreus (snake pipefish) dominated in 2007. Multidimensional scaling (MDS) identified three distinct larval assemblages in 2016 and two in 2007. Multivariate statistical analyses confirmed significant interannual differences in community composition, driven largely by environmental conditions, with depth emerging as the most influential factor, closely associated with variations in temperature and salinity. Despite the temporal gap, the findings highlight the enduring value of archived plankton survey data for detecting long-term ecological changes in larval fish communities. Such insights are vital for understanding ecosystem variability, setting conservation priorities, and guiding sustainable fisheries management under changing oceanographic conditions.